Post-Exposure Rabies Vaccine Compliance and Reasons for Non-Adherence - A Mixed Method Study in Puducherry - Sowbarnika , Vaishnavi; Aswathy Raveendran K; Premanandh K; Arulmozhi, M (National Journal of Community Medicine, 2024)
Background: Among the people who die annually of rabies worldwide, the majority either did not receive post-exposure prophylaxis (PEP), or received PEP after substantial delays or were administered PEP according to schedules that deviated from WHO recommendations. This study focuses on post-exposure rabies vaccine compliance and on the reasons for non-adherence. Methods: A mixed-method study was done among people exposed to animal bite who visited a PHC during January to December 2022.The participant list was taken from the register maintained at PHC and the data was collected by semi-structured questionnaire followed by in-depth interview. Results: The major cause for noncompliance with the ARV vaccination was failure to remember ARV schedule (52.4%), followed by lack of awareness of animal bite (19.6%) poor knowledge of ARV completion (16.2%), lack of time and access (9.4%) and choice of native treatment (2.4%). On multivariate analysis of the factors influencing rabies vaccine compliance, age, area of residence and socio-economic status were found to be statistically significant. Conclusion: The study results highlight the importance of imparting health education to increase vaccine compliance to prevent rabies.